(untitled) (International relations and international law Journal, 2016)
This article is devoted to the events in the Arab world (Arab spring), their causes and consequences. Dictatorship regimes held power through violence and deceit for decades, openly engaged in embezzlement. The masses eked out a semi-starvation, unemployment among the educated youth reached 40%. Arab woman starts fighting against the regime. Many regimes have been swept away. However, Islamic parties come to power and introduce their beneficial order, which is resisted. A newly elected president of Egypt is arrested within a year and situation in the country becomes tense. Events in Syria caused the unleashing of a civil war. Under the auspices of Russia and China, Syria starts using chemical weapon. Under the threat of U.S. bombardment, Syria (and Russia) had to transfer its chemical weapons to international control. Arab Spring events have local and spontaneous character.